2014
DOI: 10.7205/milmed-d-13-00472
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis ofStaphylococcus aureusInfections at a Military Medical Center Using the PLEX-ID Combined Polymerase Chain Reaction-Mass Spectrometry System

Abstract: Staphylococcus aureus (S. aureus) is a major cause of morbidity in the military health care setting. Culture-based methods are the most common means of identifying infections caused by this agent. However, culture-based methods lack sensitivity and specificity. The Abbott PLEX-ID instrument uses a combination of the polymerase chain reaction and mass spectrometry for the identification of bacterial isolates. We investigated whether the Abbott PLEX-ID system could identify S. aureus in clinical material and fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
1
0
2
Order By: Relevance
“…Interestingly, for the first time in this study ST107 MRSA has been reported which is similar to MRSA C18 strain that was first reported from respiratory isolate in Florida in 1997. Another ST 107 MSSA variant from wound isolates was reported in United States in 2014 [29]. Thus, globally this is the second report of ST107 MRSA clinical isolate.…”
Section: Discussionmentioning
confidence: 92%
“…Interestingly, for the first time in this study ST107 MRSA has been reported which is similar to MRSA C18 strain that was first reported from respiratory isolate in Florida in 1997. Another ST 107 MSSA variant from wound isolates was reported in United States in 2014 [29]. Thus, globally this is the second report of ST107 MRSA clinical isolate.…”
Section: Discussionmentioning
confidence: 92%
“…La mayoría de los estudios encontrados tenía un diseño retrospectivo y solo en uno se recurrió a la vigilancia prospectiva para la colonización de SAMR en todos los individuos que residían en un solo entorno militar. En otros países, se han reportado casos en la población militar (14)(15)(16)(17)(18)(19)(20)(21)(22)(23). No obstante, en nuestro país no hay información estadística en este sentido hasta la fecha.…”
Section: Discussionunclassified
“…En el presente estudio, los tejidos blandos fueron el foco de infección más frecuentemente relacionado con el desarrollo de bacteriemia por SAMR, seguido del pulmonar (figura 1). En el estudio de Laupland, et al, los principales focos infecciosos se localizaron en las zonas pélvica y en la abdominal (25 %), el aparato respiratorio (16 %), y los tejidos blandos (10 %), así como los debidos a intervenciones endovasculares (8 %) o los huesos y articulaciones (7 %) (15). Aunque en ambos estudios la mayoría de los focos de infección primaria fueron los mismos, se registraron diferencias en cuanto a la frecuencia de presentación, lo cual podría tener relación con el tipo de población evaluada, ya que, en el presente estudio, la mayor frecuencia se registró en pacientes militares activos, personal que está expuesto a las lesiones de piel.…”
Section: Discussionunclassified